Mild and Efficient Method for Aromatization of Hantzsch Esters of 1,4-Dihydropyridines with HIO3 - ZEYNIZADEH, BEHZAD; AKBARI DILMAGHANI, KARIM; MIRZAEI, MANSOOR (Asian Journal of Chemistry, 2010)
Aromatization of Hantzsch esters of 1,4-dihydropyridines was carried out efficiently by iodic acid, HIO3, in refluxing CH3CN. The corresponding pyridine compounds were obtained in quantitative yields within 7-55 min.